Persistent luminescence phosphor as in-vivo light source for tumoral cyanobacterial photosynthetic oxygenation and photodynamic therapy - Chang, Meiqi; Feng, Wei; Ding, Li; Zhang, Hongguang; Dong, Caihong; Chen, Yu; Shi, Jianlin (Bioactive materials, 2022)
Tumor oxygenation level has been regarded as an attractive target to elevate the efficiency of photodynamic therapy (PDT). Cyanobacterial photosynthesis-mediated reversal of tumor hypoxia could enable an oxygen-boosted PDT, but is limited by scant penetration depth and efficiency of external light. Herein, aiming at the dual purposes of reducing biological toxicity induced by long-term light irradiation and alleviating hypoxia, we here introduce a novel-designed CaAl2O4:Eu,Nd blue persistent luminescence material (PLM) as the in vivo light source after pre-excited in vitro. The ingenious construction of blue-emitting PLM with “optical battery” characteristics activates cyanobacterial cells and verteporfin simultaneously, which performs the successive oxygen supply and singlet oxygen generation without the long-term external excitation, resulting in the modulated tumor hypoxic microenvironment and enhanced photodynamic tumor proliferation inhibition efficiency. Both in vitro cellular assessment and in vivo tumor evaluation results affirm the advantages of self-produced oxygen PDT system and evidence the notable antineoplastic outcome. This work develops an irradiation-free photosynthetic bacteria-based PDT platform for the optimization of both oxygen production capacity and light utilization efficiency in cancer treatment, which is expected to promote the clinical progress of microbial-based photonic therapy. A distinct exogenous “irradiation-free” cyanobacteria-based PDT platform is rationally engineered for ameliorating the tumor hypoxic microenvironment and achieving the successive singlet oxygen (1O2) generation without the need of exogenous light excitation, which provides a specific paradigm of microbial-based nanotherapy with the assistance of rational design, engineering and integration of persistent luminescence phosphors as the desirable light irradiation source. [Display omitted] •Construction of CaAl2O4:Eu,Nd PLM to generate 1O2 without the aid of exogenous light excitation.•Cyanobacteria with light-triggered oxygenation effect were employed for the normalization of tumor microenvironment.•A distinct exogenous “irradiation-free” cyanobacteria-based PDT platform was rationally engineered.